Mapping Students’ Creative Thinking in Geometry: A Cognitive Style-Based Needs Analysis - Hendri Handoko; St Budi Waluya; Wardono Wardono; Sugiman Sugiman (Journal of General Education and Humanities, 2026)
Creative thinking is a key objective in geometry learning, yet prior studies have focused more on instructional interventions than on students’ initial profiles. This study aims to map students’ creative thinking in geometry and examine its variation across cognitive styles. A descriptive survey with comparative analysis was conducted involving 62 undergraduate students at UIN Siber Syekh Nurjati Cirebon. Creative thinking was measured using the Creative Thinking in Geometry Test (CTGT), covering fluency, flexibility, originality, and elaboration, while cognitive styles were classified into Field Independent (FI) and Field Dependent (FD). Data were analyzed using descriptive statistics and independent samples t-tests. The results indicate uneven performance across the dimensions, with fluency the highest and originality the lowest. Most students demonstrated moderate levels of creative thinking. FI students performed significantly better in fluency, flexibility, and originality than FD students, while no significant difference was found in elaboration. These findings suggest that cognitive style influences students’ engagement with geometry tasks and highlight the importance of identifying students’ initial profiles to inform instructional design.